The Relationship between Paraphrasing and Text Analysis - María Luisa Cepeda Islas; María del Refugio López Gamiño; Carlos Santoyo Velasco (Universidad Autónoma de Baja California, 2013)
Given the importance of paraphrasing in the process of comprehension for college students, this study assessed the level of implementation of text analysis and paraphrases the response of a sample of senior students of the career psychology. We selected a group of freshmen to the Psychology course, which was asked to answer a questionnaire and carry out the summary of an empirical article. The results showed that participants have a low level of text analysis, at the same time had low levels of paraphrasing. It was seen that the predominant textual copy. They envision some possibilities for the structure of a training workshop not only paraphrasing but on the analysis of text.